The application of the OECD Model Tax Convention to partnerships : a critical analysis of the report prepared by the OECD Committee on Fiscal Affairs /: a critical analysis of the report prepared by the OECD Committee on Fiscal Affairs. (2000) - Unknown
No abstract available